Optimalisasi Penerapan Rekam Medis Elektronik di Puskesmas Sungai Andai - Ningsih, Eka Rahma (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
ABSTRACT All health service facilities, including Community Health Centers, must implement Electronic Medical Records in accordance with the provisions no later than 31 December 2023. Optimizing the implementation of electronic medical records, there are still conditions that do not yet meet the aspects of RME implementation, Sungai Anda Public Health Center had implemented the implementation of electronic medical records already in progress in 2024, but it is still being held in a hybrid manner so there is a need to optimize the application of electronic medical records. This research uses descriptive qualitative research, data collection is carried out through interviews and observation. The subjects in this study were 4 people in the categories of Head of Community Health Center, Head of Administration, Head of medical records unit, and Registration Officer. The results of this research from the aspect of human resources in terms of quantity are still insufficient, in terms of quality, training has been provided for personnel who do not have a DIII Medical Records educational background. The hardware aspect is not sufficient for all service sub-units, the software already uses e-pukesmas. Standard operating procedures are not yet available so currently we only use guidelines from the training organizer. In this case, the implementation of electronic medical record services at the Sungai Andai Community Health Center still needs optimization to support the implementation of Electronic Medical Records. Keywords : Optimization, Implementation, Electronic Medical Records